Mygalomorph spiders of the Natural and Historical Reserve of Isla Martín García, de La Plata river, Argentina - Ferretti, Nelson Edgardo (2010)
Martín García I. is located in the upper La Plata River, at the outlet of the Uruguay River, northeastern Buenos Aires Province, Argentina. Due to its status as a protected area, it is imperative to know the biological diversity that is intended to be preserved. Mygalomorph spiders have life-history characteristics that parallel general characteristics of well-studied taxa that are “extinction prone”, either at the population or species level. We analyzed the abundance and distribution in space and time of mygalomorph spiders at the specific level. We also offer some comments of distributional patterns in a geological context. Spider abundances were sampled from Mar. 2004 to Nov. 2006 by hand-capture and pitfall traps in 5 different ecological areas. To determine the habitat preference of the species, we used the Kruskal-Wallis one-way ANOVA test. Species of the Mygalomorphae occurring on Martín García I., Actinopus sp. (Actinopodidae), Catumiri argentinense (Theraphosidae), Stenoterommata platensis (Nemesiidae), and Xenonemesia platensis (Microstigmatidae) were distributed among all habitats, with 1 specialist in only 1 habitat type. Xenonemesia platensis showed a restricted distribution possibly influenced by the geological history related with the Río de la Plata Craton as for S. platensis. Other distributional patterns may have been affected by more-recent transgressions and regressions of the sea through the Río de la Plata River.